Beyond Organizational Guidelines: Toward a Model Federal Corporate Criminal Code - Leonard Orland (Washington University Law Quarterly, 1993)
In an effort to stimulate discussion on the policy choices that Congress should have (but has not) made concerning corporate crime, and in an effort to underscore how deeply the Guidelines arrogate to the Commission basic policy matters that are more properly within the business of Congress, I propose a Model Federal Corporate Criminal Code. This Code is designed to function either independently of, or in conjunction with, a sentencing commission and is based on a number of explicit policy preferences.
Keywords: Criminal liability of juristic persons; Sentencing guidelines (Criminal procedure)